1,2,4,5-Tetrazinyl-Substituted Amino-1,2,4,5-Tetrazines - Breiner, Megan M.; Chavez, David E.; Myers, Thomas W.; Gilardi, Richard D. (Synlett, 2015)
The synthesis of 1,2,4,5-tetrazinylamino-1,2,4,5-tetrazines is reported, including the preparation of compounds containing three tetrazine heterocycles in a single compound. These materials were compared to phenylamine derivatives, also synthesized in this study. The UV/Vis and cyclic voltammetry data were collected and are reported, along with the crystal structure of one of the tritetrazine compounds.
Keywords: tetrazines; heterocycle; cyclic voltammetry; UV/Vis; nucleophilic addition